Pengaruh Kepercayaan, Kualitas Informasi Dan Persepsi Resiko Terhadap Keputusan Pembelian Di Media Sosial Instagram (Studi Kasus Pada Mahasiswa FEB UNISMA) - Ahmad Faruq Al Hafiz; Muhammad Mansur; Khalikussabir Khalikussabir (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract On online shopping sites, there are many fictitious online sellers who market fictitious products as well. A buyer must first check the existence of an online seller. Usually on an online shopping site, the site will display information about sellers whose "stalls" are often accessed by people. Buyers can take advantage of this information so as not to be deceived. Risk perception also determines someone in making purchases on Instagram. The higher risk perception causes a person to have a higher fear when transacting online, and vice versa. The various concerns of e-commerce transactions can be psychological, legal, or economic. Fear of being deceived, unsatisfactory, sometimes long delivery and confusing ordering system. the more someone trusts an online shop, the smaller the perceived risk associated with online purchases, the higher consumer confidence in online shopping sites will reduce the perceived risk of consumers in online shopping transactions. Keywords:........ Trust, Information Quality, Risk Perception, Purchase Decision